Growth and development of lower limb muscle and ball kicking performance in male soccer players - Teshima, T.; Tsunoda, N. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The purpose of this study was to investigate the effect of lower limb muscle size on ball kicking performance in Japanese male soccer players. Methods One hundred thirty-eight Japanese male soccer players aged from 12 to 22 years old were participated as subject. The subjects were classified three groups (JG: Junior high school group, n=43. HG: High school group, n=18. UG: University group, n=77). Muscle thickness of TA (thigh anterior including rectus femoris : RF and vastus intermedius : VI) and TP (thigh posterior) were measured by Ultrasonography method (SSD-900, Aloka). Three cross-sectional planes were imaged at 30%, 50% and 70% of femur length from trochanter major to lateral condyle of femur, starting at the trochanter major. In all subjects, the maximal kicked ball velocity (BV) was measured by Rader gun (Mizuno, Japan.) in distance of 5m with the three trials. The ratio of RF and VI (RF/VI ratio) was calculated in all the subjects. Results Muscle thickness of TA was showed significantly wider in 30% than 50% and 70% in each group. There were significant differences between 30%, 50% and 70% in muscle thickness values of VI and RF in each group. RF/VI ratio was obtained significantly lower value in 70% than 30% and 50% in each group. Muscle thickness of TA was showed significantly higher in UG than JG and HG in measured all site. Muscle thickness of RF at 50% was significantly differed in each age group. Whereas, there were not significant differences between JG and HG in 70% RF muscle thickness and HG and UG in 30% RF muscle thickness. RF/VI ratio was not significant difference in 70%, however significantly higher ratios in JG were observed in 30 and 50%. BV was showed higher value in UG than the other groups. In JG, TA muscle thickness was significantly correlated to the BV in measured all site. And also, muscle thickness of RF was closely related to the BV in JG. Discussion Muscle thickness of TA at 30% was showed higher value than the other sites in all groups. RF muscle thickness at 30% was increased from JG to HG, In case of 70% site RF muscle thickness was increased from HG to UG. It means that the growth of muscle in RF may be differed by site in lower limb. AT muscle thickness was closely related to the ball kicking performance in JG. And also, Muscle thickness of RF correlated to the kicked ball velocity in JG, whereas muscle thickness of VI was not related to the kicked ball velocity in all the age groups. From these results, it was suggested that level of muscle growth might be affected on ball kicking performances in adolescent soccer players. Reference Masuda K, Kikuhara N, Takahashi H, Yamanaka K. (2003) J Sports Sci, 21 851-858. Masuda K, Kikuhara N, Demura S, Katsuta S, Yamanaka K. (2005) J Sports Med Phys Fitness, 45(1) 44-52.